Development and Performance of a Multi-Fuel Residential Boiler Burning Agricultural Residues - Vamvuka, Despina; Loukeris, Dimitrios; Stamou, Evaggelos; Vlasiadis, Aristotelis; Sfakiotakis, Stelios; Bandelis, Grigorios (Frontiers in Energy Research, 2020)
The combustion behavior of selected agricultural residues (olive and peach kernels, almond and walnut shells) and their blends was investigated in a prototype low-investment combustion unit of nominal capacity 65 kWth. Blending ratio for olive kernel was 50 or 70%, while for the rest of the residues 30 or 50%. Flue gas temperatures, inlet and outlet water temperatures of the boiler and gaseous emissions were measured at specific feed and air flow rates and combustion and boiler efficiencies were determined. CO and NOx emissions from all fuels during the whole operation of the unit were below legislation limits, while SO2 emissions were negligible. Combustion efficiencies were satisfactory, ranging between 84 and 86%. Peach kernels burned with the highest efficiency. By blending olive kernels with peach kernels, almond or walnut shells at percentages up to 50%, the overall efficiency of the system in terms of emissions and degree of combustion was improved, achieving the best performance with olive kernels/peach kernels 50:50 blend. Co-combustion of unpelletized materials could be predicted to a great extent from the combustion of component fuels, offering apart from environmental and economic benefits.